Global modernity and social contestation - Bringel, Breno M.; Domingues, José Maurício (London SAGE Publications Ltd, 2015)
A key resource for research in both social theory and the sociology of modernity, as well as social movements and social contestation, and for those interested in globalization and global studies.
Part I. Rethinking modernity through social contestation -- Part II. Rethinking social contestation through modernity -- Part III. Borders of modernity and frontiers of exclusion : rights, citizenship and contestation in comparative perspective.
Includes bibliographical references and index.
Keywords: Social movements; Civilization, Modern; Social conflict